A recurrent clonally distinct Burkitt lymphoma case highlights genetic key events contributing to oncogenesis. Issue 8 (27th March 2019) - Penther, Dominique; Viailly, Pierre‐Julien; Latour, Sylvain; Etancelin, Pascaline; Bohers, Elodie; Vellemans, Hélène; Camus, Vincent; Menard, Anne Lise; Coutant, Sophie; Lanic, Hélène; Lemasle, Emilie; Drieux, Fanny; et al.
Abstract: Burkitt lymphoma (BL) is characterized by a translocation of the MYC oncogene that leads to the upregulation of MYC expression, cell growth and proliferation. It is well‐established that MYC translocation is not a sufficient genetic event to cause BL. Next‐generation sequencing has recently provided a comprehensive analysis of the landscape of additional genetic events that contribute to BL lymphomagenesis. Refractory BL or relapsing BL are almost always incurable as a result of the selection of a highly chemoresistant clonally related cell population. Conversely, a few BL recurrence cases arising from clonally distinct tumors have been reported and were associated with a favorable outcome similar to that reported for first‐line treatment. Here, we used an unusual case of recurrent but clonally distinct EBV+ BL to highlight the key genetic events that drive BL lymphomagenesis. By whole exome sequencing, we established that ID3 gene was targeted by distinct mutations in the two clonally unrelated diseases, highlighting the crucial role of this gene during lymphomagenesis. We also detected a heterozygous E1021K PIK3CD mutation, thus increasing the spectrum of somatic mutations altering the PI3K signaling pathway in BL. Interestingly, this mutation is known to be associated with activated phosphoinositide 3‐kinase delta syndrome (APDS). Finally, we also identified an inherited heterozygous truncating c.5791CT FANCM mutation that may contribute to the unusual recurrence of BL.